2015
DOI: 10.1186/s40064-015-1288-9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of hybrid hydrazino peptides: protected vs unprotected chiral α-hydrazino acids

Abstract: Peptidomimetics based on hydrazino derivatives of α-amino acids represent an important class of peptidic foldamers with promising biological activities, like protease inhibition and antimicrobial activity. However, the lack of straightforward method for the synthesis of optically pure hydrazino acids and efficient incorporation of hydrazino building blocks into peptide sequence hamper wider exploitation of hydrazino peptidomimetics. Here we described the utility of Nα-benzyl protected and unprotected hydrazino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…The absence of long-range NOE contacts indicates a lack of a well-defined secondary structure (Figure B). Indeed, the final NMR structural ensemble revealed that the parent peptide adopts an extended conformation with local structuring in the form of a γ-turn (Figure C), which could be attributed to the influence of the C-terminal amide (−C­(O)­NH 2 ) group on the local organization . Similar features were reported by Garcia-Echeverria et al for a dodecapeptide, containing the full sequence of the parent peptide, with the formation of an extended or random coil backbone conformation in aqueous solution …”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The absence of long-range NOE contacts indicates a lack of a well-defined secondary structure (Figure B). Indeed, the final NMR structural ensemble revealed that the parent peptide adopts an extended conformation with local structuring in the form of a γ-turn (Figure C), which could be attributed to the influence of the C-terminal amide (−C­(O)­NH 2 ) group on the local organization . Similar features were reported by Garcia-Echeverria et al for a dodecapeptide, containing the full sequence of the parent peptide, with the formation of an extended or random coil backbone conformation in aqueous solution …”
Section: Resultssupporting
confidence: 79%
“…Hydrazino derivatives of phenylalanine, leucine, and tyrosine were prepared by nucleophilic substitution of d -amino acid-derived α-bromo acid with hydrazine hydrate ( Scheme 1 , with the details in the Supporting Information ). 35 , 45 In the final step, the N β atom was masked with an Fmoc protecting group. Fmoc derivatives of α-hydrazino acids were recrystallized and used in a solid-phase peptide synthesis (SPPS).…”
Section: Resultsmentioning
confidence: 99%
“…N a -Benzyl, N b -Boc protected hydrazino acids (type I, Scheme 2) were obtained by electrophilic amination of the corresponding N-benzyl-L-amino acid with N-Boc oxaziridine. 22 Nucleophilic substitution of D-amino acid-derived a-bromo acid with Boc-hydrazine yielded N b -Boc protected a-hydrazino acids, 23 where N a position was further protected with Boc (type II) or Cbz group (type III, Scheme 2). 24 Also, hydrazino proline derivative, Boc-hPro-OH (Scheme 2) was used to explore the utility of cyclic acid components in the Passerini reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Besides this, the introduction of the hydrazino group into several classes of compounds presents several advantages. For instance, hydrazinopeptides comprise a class of peptidomimetics with promising biological and conformational activities [ 18 21 ]. It is worth mentioning that in such compounds the so-called "hydrazino-turns" are formed through intramolecular hydrogen bonding between the hydrazino groups.…”
Section: Introductionmentioning
confidence: 99%